Investigation of Fluid Flow and Heat Transfer Characteristics of an Internally Channeled Tube Heat Exchanger under Laminar Flow Conditions - Al-Lami, Abbas Jarullah Sangoor; Kenig, Eugeny Y. (energies)

§ 78 (Kartellrechtliche Grenzen der stillen Gesellschaft) - Bartlitz, David (Münchener Handbuch des Gesellschaftsrechts)

§ 6 (Kartellrechtliche Grenzen der Kommanditgesellschaft) - Bartlitz, David (Münchener Handbuch des Gesellschaftsrechts)

Measurement of Ultrashort Biphoton Correlation Times with an Integrated Two-Color Broadband SU(1,1)-Interferometer - Roeder, Franz; Pollmann, René; Stefszky, Michael; Santandrea, Matteo; Luo, Kai Hong; Quiring, V.; Ricken, Raimund; Eigner, Christof; Brecht, Benjamin; Silberhorn, Christine (PRX Quantum)
The biphoton correlation time, a measure for the conditional uncertainty in the temporal arrival of two photons from a photon pair source, is a key performance identifier for many quantum spectroscopy applications, with shorter correlation times typically yielding better performance. Furthermore, it provides fundamental insight into the effects of dispersion on the biphoton state. Here, we show that a characteristic dependence of the width of the temporal interferogram can be exploited to obtain insights into the amount of second-order dispersion inside the interferometer and to retrieve actual and Fourier-limited ultrashort biphoton correlation times of around 100 fs. In the presented scheme, we simultaneously measure spectral and temporal interferograms at the output of an SU(1,1) interferometer based on an integrated broadband parametric down conversion source in a Ti:LiNbO3 waveguide.

Doing language im Deutschunterricht. Eine Analyse sprachbezogener Adressierungen in diskursiver Praxis - Büttner, Denise
Die Studie leistet einen empirisch-rekonstruktiven Beitrag zu einer machtkritisch ausgerichteten Fachdidaktik. Sie fokussiert den Deutschunterricht und die darin stattfindenden Interaktionen als diskursive Praxis, in der ein spezifisches Wissen in, über und angesichts von Sprache relevant gemacht wird. Für Subjektivierung ist jenes Wissen hochgradig wirkmächtig und bleibt den Akteur*innen im Prozess der schulischen Enkulturation doch größtenteils unbewusst. Darin liegt ein hohes Potential für die institutionelle (Re-)Produktion von Linguizismus.Vor diesem Hintergrund eröffnet die Studie einen Blick auf sprachbezogene Adressierungen, die in charakteristischer Weise vom Fach selbst ausgehen. Sie werden in (fach)didaktischen und pädagogischen Programmatiken breit kommuniziert und zeichnen sich bis auf die Ebene unterrichtlicher Praktiken ab. Um das Zusammenspiel von fachspezifischer Adressierung und Praktiken des ‚doing language‘ möglichst eng aufeinander beziehen und in rekonstruktionslogisch plausibilisierte Zusammenhänge bringen zu können, liegt der Arbeit ein wissenssoziologisch-diskursanalytischer Ansatz zugrunde.
Keywords: Diskursanalyse; Machtkritik; Sprache und Bildung; Rekonstruktive Unterrichtsforschung; Subjektivierung; Fachdidaktik

Exploratory Landscape Analysis for Mixed-Variable Problems - Prager, Raphael Patrick; Trautmann, Heike (IEEE Transactions on Evolutionary Computation)
Keywords: Optimization; Evolutionary computation; Benchmark testing; Hyperparameter optimization; Portfolios; Extraterrestrial measurements; Dispersion; Exploratory landscape analysis; mixed-variable problem; mixed search spaces; automated algorithm selection

Exploring data-driven model-based systems engineering: a systematic literature review - Tissen, Denis; Wiederkehr, Ingrid; Koldewey, Christian; Dumitrescu, Roman (2023 IEEE International Conference on Technology Management, Operations and Decisions (ICTMOD))

ESLM: Improving Entity Summarization by Leveraging Language Models - Firmansyah, Asep Fajar; Moussallem, Diego; Ngonga Ngomo, Axel-Cyrille (The Semantic Web)

Computing Repairs Under Functional and Inclusion Dependencies via Argumentation - Mahmood, Yasir; Virtema, Jonni; Barlag, Timon; Ngonga Ngomo, Axel-Cyrille (Lecture Notes in Computer Science)

Navigating Transparency: The Influence of On-demand Explanations on Non-expert User Interaction with AI - Papenkordt, Jörg (Artificial Intelligence in HCI)

“Paving the way for student-led publication: Development and implementation of a course in Information Systems with open educational resources - Althaus, Maike; Müller, Michelle; Bartelheimer, Christian; Kundisch, Dennis

Assessing the impact of organizational culture on workarounds: A maturity model - Bartelheimer, Christian; Reineke, Malte

Hybridizing Target- and SHAP-encoded Features for Algorithm Selection in Mixed-variable Black-box Optimization - Dietrich, K.; Prager, R.; Doerr, C.; Trautmann, Heike (Parallel Problem Solving from Nature — PPSN XVIII)

Michael Basse / Marcel Nieden (Hg.): Cajetan und Luther. Rekonstruktion einer Begegnung. Tübingen 2021 - Schroeter-Wittke, Harald (Jahrbuch für Evangelische Kirchengeschichte des Rheinlandes)

Lorenz Trein: Beobachtungen der Säkularisierung und die Grenzen der Religion. Tübingen 2023 - Schroeter-Wittke, Harald (Jahrbuch für Evangelische Kirchengeschichte des Rheinlandes)

Highly Efficient Quenching of Singlet Oxygen by DNA Origami Nanostructures - Garcia-Diosa, Jaime Andres; Grundmeier, Guido; Keller, Adrian (Chemistry – A European Journal)
DNA origami nanostructures (DONs) are able to scavenge reactive oxygen species (ROS) and their scavenging efficiency toward ROS radicals was shown to be comparable to that of genomic DNA. Herein, we demonstrate that DONs are highly efficient singlet oxygen quenchers outperforming double‐stranded (ds) DNA by several orders of magnitude. To this end, a ROS mixture rich in singlet oxygen is generated by light irradiation of the photosensitizer methylene blue and its cytotoxic effect on Escherichia coli cells is quantified in the presence and absence of DONs. DONs are found to be vastly superior to dsDNA in protecting the bacteria from ROS‐induced damage and even surpass established ROS scavengers. At a concentration of 15 nM, DONs are about 50 000 times more efficient ROS scavengers than dsDNA at an equivalent concentration. This is attributed to the dominant role of singlet oxygen, which has a long diffusion length and reacts specifically with guanine. The dense packing of the available guanines into the small volume of the DON increases the overall quenching probability compared to a linear dsDNA with the same number of base pairs. DONs thus have great potential to alleviate oxidative stress caused by singlet oxygen in diverse therapeutic settings.

Children and young people’s ICT experiences in school education: Participatory research design to engage children and young people as experts in research - Labusch, Amelie; Eickelmann, Birgit; Casamassima, Gianna; Drossel, Kerstin; Gudmundsdottir, G.B.; Kazani, A.; Mifsud, L.; Symeonaki, M.; Teidla-Kunitsõn, G. (Understanding the everyday digital lives of children and young people)

Perspectives of children and young people on their education as preparing for their future in the digital age: In-depth qualitative study in five European countries. - Eickelmann, Birgit; Barbovschi, M.; Holmarsdottir, H.B.; Parsanoglou, D.; Sisask, M.; Labusch, Amelie (Understanding the everyday digital lives of children and young people)

Theorien des digitalen Kapitalismus - Fuchs, Christian (Handbuch Medientheorien im 21. Jahrhundert)

On the Potential of Multi-objective Automated Algorithm Configuration on Multi-modal Multi-objective Optimisation Problems - Preuß, Oliver Ludger; Rook, Jeroen; Trautmann, Heike (Applications of Evolutionary Computation)